Impacts of a weir and power station on downstream migrating Atlantic salmon smolts in a German river - Havn, Torgeir Børresen; Thorstad, Eva Bonsak; Borcherding, Jost; Heermann, Lisa; Teichert, Maxim A. K.; Ingendahl, Detlev; Tambets, Meelis; Sæther, Stein Are; Økland, Finn (River Research and Applications, 2020)
Weirs are barriers built across rivers for a wide range of other purposes than hydropower production. Like hydropower installations, weirs can negatively impact fish migrations. Downstream migration and mortality of Atlantic salmon smolts were studied during passage of a weir and power station by tagging 227 smolts with radio transmitters. Extra loss of smolts due to the weir and adjacent reservoir was 5.2%. Mortality was likely related to physical damage imposed to the smolts and/or increased predation risk. Extra loss of smolts did not differ between the weir and the power station (7.2%). Migration speeds were reduced at the power station but not at the weir. We conclude that mortality at one power station site may differ considerably among years, because the mortality was more than four times higher in a previous year than in this study. Increased river discharge seemed to decrease mortality and increase migration speeds at the power station.